Evisceration Versus Enucleation in Ocular Globe Injury - Nasyayya Akbari Nazar; Hendriati (Bioscientia Medicina : Journal of Biomedicine and Translational Research, 2022)
Evisceration and enucleation have been acceptable therapeutic modalities to treat not only severe ocular trauma but also various ocular conditions, such as intraocular tumors, endophthalmitis, and blind-painful-cosmetically disfiguring eyes, over the last two centuries. Clinical indications and choices of procedure, whether enucleation or evisceration, vary among institutions, surgeon experience, and severity of structure loss. In the past, enucleation has been preferred by most surgeons for various reasons, including the fear of sympathetic ophthalmia (SO) after evisceration. Despite the possibility of causing SO, anophthalmic socket also has complications, including superior sulcus defect, conjunctival surface changes, implant exposure, fornix/socket contraction, and eyelid malposition. This literature review will discuss indication, technique, and decision with regard to enucleation or evisceration after ocular trauma.